Two Rulers by the Name Ur-Ningirsu in Pre-Ur III Lagash - Maeda, Tohru
copy and photo of BM 18474; p.25-31: Year Formulas (1) mu é-dnin-gír-su-ka ba-dù-a: (2) mu lù-maḫ-dinanna maš-eì-pà; (3) mu èš-gán-lugal šà gir-suki-ke4 ba-ta-è.